Analisis Penerapan Akuntansi Lingkungan (Green Accounting) pada Pengelolaan Limbah Industri di PT Atsumitec Indonesia - Svetlana Puteri Kirana; Lilis Lasmini; Rohma Septiawati (Al-Kharaj: Jurnal Ekonomi, Keuangan & Bisnis Syariah, 2024)
This research primarily investigates the application of environmental accounting, often known as green accounting, in the management of industrial waste. Ecological accounting is an accounting system that incorporates environmental factors into the process of making economic decisions. The objective of this study is to investigate the application of environmental accounting in waste management for the purposes of cost reduction, delineation of environmental responsibilities within the organization, and generation of environmental cost reports to facilitate decision-making by management. This study employs a comparative descriptive methodology, including data collection methods such as interviews, archival recordings, and direct observation. Research findings indicate that PT Atsumitec Indonesia currently lacks a dedicated financial report for waste management. Thus, in order to effectively manage accountability, this study must include environmental accounting methods for waste management.